The Influence Of Job Description And Motivation On Performance Management Of Student Corporation Perjuangan Insan Madani - Rahmi Nurhaliza; Cece Rakhmat; Arga Sutrisna (Penerbit Jurnal Indonesia, 2022)
This study aims to find out and understand the Job Description and Motivation for the Performance Management of Student Corporation Perjuangan Insan Madani. This type of research is quantitative research with a descriptive approach. The type of data used in this study was primary data and samples taken by 42 corporation management. Data collection techniques using questionnaires. Analytical techniques in data processing use multiple linear regression. Based on the results of hypothesis testing, Job Description and Motivation both simultaneously and partially have a significant effect on the Performance Management of Student Corporation Perjuangan Insan Madani.